2022
DOI: 10.3390/life12071064
|View full text |Cite
|
Sign up to set email alerts
|

Association between Usual Dietary Intake of Food Groups and DNA Methylation and Effect Modification by Metabotype in the KORA FF4 Cohort

Abstract: Associations between diet and DNA methylation may vary among subjects with different metabolic states, which can be captured by clustering populations in metabolically homogenous subgroups, called metabotypes. Our aim was to examine the relationship between habitual consumption of various food groups and DNA methylation as well as to test for effect modification by metabotype. A cross-sectional analysis of participants (median age 58 years) of the population-based prospective KORA FF4 study, habitual dietary i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…To explore the stability of associations of usual dietary intake of food groups and DNA methylation, we analyzed those food group-CpG associations in the KORA Fit study that were reported as significant in an earlier analysis of our team in KORA FF4 (6). Overall, few results could be reproduced in KORA Fit (Table 3), i.e., reached statistical significance; however, with a much smaller sample size as available in KORA FF4.…”
Section: Cross-sectional Reproduction Of Kora Ff In Kora Fitmentioning
confidence: 99%
See 2 more Smart Citations
“…To explore the stability of associations of usual dietary intake of food groups and DNA methylation, we analyzed those food group-CpG associations in the KORA Fit study that were reported as significant in an earlier analysis of our team in KORA FF4 (6). Overall, few results could be reproduced in KORA Fit (Table 3), i.e., reached statistical significance; however, with a much smaller sample size as available in KORA FF4.…”
Section: Cross-sectional Reproduction Of Kora Ff In Kora Fitmentioning
confidence: 99%
“…The first studies on diet and DNA methylation were conducted in cancer patients because of the known association between cancer and DNA methylation and the idea to elucidate the potentially harmful or protective effects of diet on cancer (5). Then, research started to look directly at dietary factors that influence DNA methylation and until today focused heavily on micronutrients such as folic acid or B vitamins (6). Mandaviya et al (7) showed associations between dietary folate intake and CpG methylation in an epigenome-wide association study (EWAS), but other groups were unable to confirm these associations (8,9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the fibre intervention did not significantly change metabolic parameters across metabotypes, the group with an unfavourable profile had the greatest reductions in insulin, cholesterol parameters (total cholesterol, LDL-C and non-HDL-C) and blood pressure. These metabotypes were also applied to investigate their effect on associations between diet and DNA methylation (28) . While only a few significant associations were observed in the total cohort, many were observed when the analyses were stratified by metabotypes; most of them between methylation sites and the intake of cruciferous, cheese, whole grain products, margarine, eggs and total meat.…”
Section: Ability Of Metabotyping To Identify Differential Response To...mentioning
confidence: 99%